2016
DOI: 10.1530/erc-15-0426
|View full text |Cite
|
Sign up to set email alerts
|

IGF2 and IGF1R in pediatric adrenocortical tumors: roles in metastasis and steroidogenesis

Abstract: Deregulation of the IGF system observed in human tumors indicates a role in malignant cell transformation and in tumor cell proliferation. Although overexpression of the IGF2 and IGF1R genes was described in adrenocortical tumors (ACTs), few studies reported their profiles in pediatric ACTs. In this study, the IGF2 and IGF1R expression was evaluated by RT-qPCR according to the patient's clinical/pathological features in 60 pediatric ACT samples, and IGF1R protein was investigated in 45 samples by immunohistoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 60 publications
2
15
0
Order By: Relevance
“…However, these encouraging findings have not been confirmed in clinical trials, although a small percentage of patients showed a partial response to treatment (24). In the present series, we confirmed IGF2 overexpression in 95% of cases, whereas IGF1R was down-regulated in 45% of cases, similarly as previously described (34). Of note, however, 37.5% of cases presented high CDK4 and normal or high IGF1R mRNA levels.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…However, these encouraging findings have not been confirmed in clinical trials, although a small percentage of patients showed a partial response to treatment (24). In the present series, we confirmed IGF2 overexpression in 95% of cases, whereas IGF1R was down-regulated in 45% of cases, similarly as previously described (34). Of note, however, 37.5% of cases presented high CDK4 and normal or high IGF1R mRNA levels.…”
Section: Discussionsupporting
confidence: 71%
“…Of note, however, 37.5% of cases presented high CDK4 and normal or high IGF1R mRNA levels. On the other hand, an IGF1R overexpression is found in NCI-H295R cells in our and previous studies (33,34). Thus, with IGF1R being the main target of linsitinib, its low/absent expression in ACC might be one reason for the disappointing response rate in ACC patients (24) and pre-screening for IGF1R overexpression might then be useful to pre-select patients that may benefit from this treatment.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Many studies have found p53 expression to be frequent in malignant adrenocortical tumours . Insulin‐like growth factor 1 receptor overexpression, decreased expression of HLA‐DRA, HLA‐DPA1, and HLA‐DPB1, and major histocompatibility complex class II expression have also been suggested as a possible markers of aggressive disease in paediatric adrenocortical tumours …”
Section: Adrenocortical Carcinomas In Childrenmentioning
confidence: 99%
“…However, overall, the findings point at the same direction, which is a metabolic reprogramming towards a glycolytic phenotype in adrenocortical malignant tumors. Previous studies focusing on the biological aspects behind malignancy in pediatric ACTs have identified the insulin-like growth factor (IGF) system, specifically the pair IGF2/IGF1 receptor (IGF1R), as one of the molecular mechanisms involved in the process of tumorigenesis [ 43 46 ]. Although some of the signaling proteins downstream of IGF1R, such as Akt, mTOR and AMP-activated protein kinase (AMPK), have a pivotal role in cancer cell metabolic reprogramming [ 42 , 47 , 48 ], the possible role of IGF1R as a mediator of the Warburg effect has not been clearly established.…”
Section: Discussionmentioning
confidence: 99%